Duración de la estancia hospitalaria. Metodologías para su intervención (2014)
ABSTRACT: Prolonged hospitalization constitutes a grave concern worldwide because it generates negative effects on the health system such as, for example: increase in costs, deficient accessibility to hospitalization services, overload of emergency services, and the risk of adverse effects. This work presents a research that lists the most common causes found in the extension of the hospitalizations and the most applied hospital logistic methodologies for its study and improvement. Results: The causal agents of extended hospitalizations found with higher frequency in literature are: delay in the performance of surgical and diagnostic procedures; need for attention in another complexity level; social-family situation, and the age of the patient. We con- clude that to analyze the problem of hospitalizations it is convenient to perform an “adjustment for risk”, using the method of the related diagnosis group (grd), and simulations are an appropriate methodology to identify bottlenecks.